Inhabiting as an Aesthetics of the Public: notes on the practice of theatrical habitation - Castro, Luciana Araújo; Caetano, Nina (Revista Brasileira de Estudos da Presença, 2020)
This article presents an excerpt from a master’s research in which the proposal was to conceptualize the practice of theatrical habitation, performed by the Teatro Público group (Belo Horizonte/MG), as both process and scenic proposition. For this purpose, the authors start from the aesthetics related to walking in order to map the theoretical field of this project, and then use other spatial practices analogous to theatrical habitation to expose their similarities and differences that justify the choice of a new nomenclature. Finally, some of the characteristics of this practice are outlined, such as the coexistence in extended temporality, as a way to think about inhabiting as an aesthetics of the public.